Maklumat perioperatif yang diterima oleh pesakit surgeri di Hospital Universiti Sains Malaysia - Muhazalina, Muhamad (PPSP, Universiti Sains Malaysia, 2007)
Patients undergoing surgery need information as a preparation, mentally and physically to cope with the real situation during the surgery. It is important because surgery is a stressful event. Detail information given during perioperative phase is useful to patients in order to perform their own self care after the operation and also may decrease their anxiety. Patient's level of understanding towards the perioperative information must be increased via clear and simple explaination so that patient will cooperate with the treatment given. Patients are entitled to know every things about their condition, progress and all the procedures that will be done to them. Therefore, as a nurse, they must ensure patients undergoing surgery receive perioperative information and it is important to ensure patients understand about the peri operative information given. Objectives: The purposes of this study are to determine the perioperative information received by patients undergoing surgery, level of patients understanding towards the information given and factors that influence information received and patient's level of understanding. Methodology: This study begins in December, 2006 until Mac 2007 that includes three surgical wards which are Wad 1 Utara, 2 Intan dan 3 Utara in Hospital Universiti Sains Malaysia (USM). Methods of sample collection is using non-randomized and purposive sample and 64 respondents had been successfully collected by the researcher.